PENGEMBANGAN KURIKULUM PAUD ISLAMI DI ACEH - Novita Fanny (Jurnal Buah Hati, 2022)
Aceh people aspire that education in Aceh to be Islamic so the learning program refer to Al-Quran and Hadist. Today, education in Aceh is preparing Islamic curriculum in accord with qanun rule applied, so the researcher analyze the foundation and principle in developing Aceh curriculum for Early Childhood Education and also analyze the component in developing Aceh curriculum for Early Childhood Education. This study used qualitative research method with case study approach. The study result showed that Aceh curriculum for Early Childhood Education has had foundation as base for curriculum development and strong principle to become guidance in implementation so it support the success of education even though it is not explained explicitly. In this Aceh curriculum, there is addition of program content in Early Childhood Education namely Islamic Education which comprise the themes of aqidah, akhlak, fikih, tarikh, Al-Quran and acehness value content which comprise the themes of aceh history, aceh language, aceh peunajoeh, aceh art and culture and geographical position of Aceh. Islamic curriculum means prioritizing akhlak. The development of Aceh curriculum for Early Childhood Education has been good, but there is a need of another thinking about the method which is more effective in children learning through akhlak building. Abstrak Aspirasi masyarakat Aceh menginginkan pendidikan di Aceh bersifat islami sehingga program pembelajaran merujuk pada Al-Quran dan hadist. Saat ini untuk pendidikan di Aceh sedang disiapkan kurikulum yang bersifat islami sesuai dengan peraturan qanun yang berlaku, sehingga peneliti menganalisis landasan dan prinsip dalam pengembangan kurikulum Aceh untuk PAUD dan juga untuk menganalisis komponen pengembangan kurikulum PAUD Aceh. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Hasil penelitian menunjukkan bahwa kurikulum PAUD Aceh sudah mempunyai landasan sebagai dasar pengembangan kurikulum dan prinsip yang kuat yang menjadi pedoman dalam pelaksanaan sehingga mendukung keberhasilan pendidikan meskipun tidak dijelaskan secara eksplisit. Pada kurikulum Aceh ini adanya tambahan muatan program pada PAUD yaitu Pendidikan Agama Islam (PAI) meliputi tema aqidah, akhlak, fikih, tarikh, Al-Quran dan Muatan nilai keacehan meliputi tema sejarah aceh, bahasa aceh, peunajoeh aceh, seni budaya aceh, letak geografis aceh. Pada kurikulum Islami berarti bersifat keislaman yaitu menggutamakan akhlak. Pengembangan kurikulum Aceh untuk PAUD ini sudah baik, tetapi perlu adanya pemikiran lain tentang metode yang lebih efektif dalam pembelajaran anak melalui pembinaan akhlak.